2019
DOI: 10.2217/cer-2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcome of induced labor by intracervical Foley catheter with misoprostol versus misoprostol alone

Abstract: Aim: To evaluate the comparative outcome of induced labor by intracervical Foley catheter with misoprostol versus misoprostol alone. Materials & methods: A total of 1306 women were enrolled over 4 years, induced with either intracervical Foley with misoprostol or misoprostol alone and compared in terms of induction-delivery interval, mode of delivery, the presence of uterine tachysystole, postpartum hemorrhage and perinatal outcome. Results: Induction to delivery interval, the duration between induction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The predominant country of origin was the United States (16 studies). 14e18,20,23e25, 27,28,33,34,39,40,42 Studies from India, 21,26,32,37,41 Egypt, 29e31 Iran, 36 Israel, 22 Nigeria, 19,43 Kenya, 38 and Pakistan 35 were also included. The specific study characteristics and outcomes are listed in Table 1.…”
Section: Obstetrics Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant country of origin was the United States (16 studies). 14e18,20,23e25, 27,28,33,34,39,40,42 Studies from India, 21,26,32,37,41 Egypt, 29e31 Iran, 36 Israel, 22 Nigeria, 19,43 Kenya, 38 and Pakistan 35 were also included. The specific study characteristics and outcomes are listed in Table 1.…”
Section: Obstetrics Original Researchmentioning
confidence: 99%
“…The overall quality of the studies included was rated as high, with 7 studies of uncertain quality. 21,22,26,29,32,36,41 Outcomes A total of 15 studies ( 2180 women) reported the time from induction to vaginal delivery. 14e17,20,22,24,26e28, 30,34,35,37,39 When compared with Foley alone, the use of Foley-oxytocin reduced the time to vaginal delivery by 4.2 hours (mean duration [MD], e4.2 hours; 95% CI, e6.5 to e1.9).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
“…It has been reported early that the overall safety of full-term parturients using oxytocin is not high, and they often suffer from complications such as cervical edema, intrauterine fetal distress, and neonatal asphyxia 11 . The application of misoprostol in the vagina has a specific risk of causing excessive uterine contraction, meconium-stained amniotic fluid, abnormal fetal heart rate, emergency cesarean section, postpartum hemorrhage, and neonatal asphyxia 12 . Dinoprostone suppository can result in persistent and uterine solid contraction, so magnesium sulfate needs to be used to inhibit uterine contraction and fetal distress can be caused in severe cases, in which case parturients need to be converted to emergency cesarean section 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, Priyadarshini et al examine the comparative outcomes of methods to induce labor -an intervention that has been reported by the WHO to be used in 25% of all deliveries in developed countries [5]. In this study, the authors compare the outcomes of a combination of the Foley bulb and misoprostol, with misoprostol alone, for induction of labor.…”
Section: In This Issuementioning
confidence: 99%
“…In their study, Du et al assess the validity and reliability of the Dundee Difficult Times of the Day Scale, a ten-question rating scale used by parents to assess their child's functional impairment throughout the day [3]. The authors compare the Dundee Difficult Times of the Day Scale with two general rating scales for the general assessment of attention-deficit/hyperactivity disorder.Real-world evidence continues to be an important source of information in outcomes research, and in the next research article, Feldman and colleagues examine real-world adherence and costs of apremilast compared with biologic agents in US psoriasis patients [4].Next, Priyadarshini et al examine the comparative outcomes of methods to induce labor -an intervention that has been reported by the WHO to be used in 25% of all deliveries in developed countries [5]. In this study, the authors compare the outcomes of a combination of the Foley bulb and misoprostol, with misoprostol alone, for induction of labor.In the final article of this issue, Murray and colleagues assess the cost-effectiveness of a range of treatments for overactive bladder, compared with best supportive care [6].…”
mentioning
confidence: 99%